Time for Puppy School - O'Connor, Jane; Enik, Ted (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2017)
When Frenchy gets in trouble one too many times, the Clancy's decide it's time for puppy school.
Keywords: Fancy Nancy -- (Fictitious character) -- Juvenile fiction; Fancy Nancy -- (Fictitious character) -- Fiction; Dogs -- Juvenile fiction; First day of school -- Juvenile fiction; Dogs -- Fiction; First day of school -- Fiction; Humorous fiction